Geochemical record of methane seepage in carbon cycling and possible correlation with climate events in the Qiongdongnan basin, South China Sea. (March 2023) - Dan, Xiaopeng; Liu, Shuang; Feng, Xiuli; Lin, Lin; Tang, Rong; Yang, Chao; Xu, Jinya; Wu, Zihan
Abstract: At cold seeps, sulfate-driven anaerobic oxidation of methane (SD-AOM) is the dominant biogeochemical process, which can significantly affect the marine carbon-sulfur cycle. In this paper, multiple sedimentary indicators in core QS-1 were reported for methane seepage from Haima seep of the South China Sea (SCS). By combining total carbon (TC), total organic carbon (TOC), total sulfur (TS), total inorganic carbon (TIC), as well as the carbon and oxygen isotope compositions of benthic foraminifera Uvigerina spp. In sediments, our aim was to explore the geochemical evidence on methane seepage activities in this area. We identified three methane release events (MREs) with different intensities and timescales during MIS 1–2, characterized by particular anomalies of negative δ 13 CTIC (as low as −41.42‰) and δ 13 C U.spp (as low as −5.50‰), high contents of TS and high S/C ratios, simultaneously. High S/C ratios and negative values of δ 13 CTIC effectively indicate the intense SD-AOM and SD-AOM-related process in core QS-1. Three MREs, occurred at high or low sea level, may due to the climate-driven increase of hydrostatic pressure and seafloor temperature. The insights for sediment carbon-sulfur trace element, carbon isotopes of TIC contents and benthic foraminifera have obvious implications for tracing past methane seepages and its possible link with climate changes. Highlights: High quality samples drilled from Haima cold seeps areas were investigated. High S/C ratios, negative δ 13 CTIC and δ 13 C U.spp revealed intense AOM process. Carbon cycling in methane history was identified using carbon isotopes. Climate-driven increase of seafloor temperature triggered MREs occurred at high sea-level.